Talking water: interplay of gender, trust and expertise in agricultural extension groups in Mendoza, Argentina - Riera, Felix Sebastián; Hunecke, Claudia; Gennari, Alejandro J. (IOP Science, 2024)
Stakeholder adaptation is a critical strategy to overcome changing climate patterns worldwide. Still it relies on the speed and effectiveness of information flow to end-users. Research shows that the loss of information in several stages of its spread and learning from peers is more important than the knowledge circulated by extension services. Women’s participation and contribution are supportive and strategic, depending on the level of agreement and the interplay of trust variables within the network. In the arid Andes, agriculture is central and dependent on water management and macroeconomic conditions that shape market prospects, irrigation practices, and stakeholder behavior. Data were collected using the platform of a capacity-building program for organisations of water users in the Diamante and Atuel River basins in Mendoza, Argentina. Social Network Analysis (SNA) contributes to unveiling the cornerstones of information flow by identifying group structures, strong bonds, and bottlenecks in water management systems. In the first step, we evaluated the characteristics (density, centrality, average shortest path, and degree) of the pre-existing relationships and five sub-topic networks. Second, we compare networks containing pre-existing links only with those formed during the lecture. Emphasizing adaptation practices to cope with climate change impacts, the results provide valuable insights into the intricate interplay of gender dynamics, trust, expertise recognition, and discussion patterns within water and agricultural extension groups in Argentina. These insights highlight the ongoing need to promote gender equity, address biases in expertise recognition, and leverage trust for meaningful knowledge exchanges within evolving social contexts. It also reveals the alignment of Argentina's gender performance with similar production setups in Southern America or the Global North, highlighting the universality of challenges and opportunities in fostering inclusive and equitable participation. Our findings indicate that each group within the two river basins exhibits numerous pre-existing links and tends to be less accessible to newcomers, resulting in a shorter average path. Thus, information can spread faster. Trust is an underlying facilitator for sensible topics and a catalyzer for communication.